2009
DOI: 10.1021/nn800726e
|View full text |Cite
|
Sign up to set email alerts
|

The Role Radius of Curvature Plays in Thiolated Oligonucleotide Loading on Gold Nanoparticles

Abstract: We show that by correlating the radius of curvature of spherical gold nanoparticles of varying sizes with their respective thiol terminated oligonucleotide loading densities that a mathematical relationship can be derived for predicting the loading of oligonucleotides on anisotropic gold nanomaterials. This mathematical relationship was tested with gold nanorods (radius 17.5 nm, length 475 nm) where the measured number of oligonucleotides per rod (3330 ±110) was within experimental error of the predicted loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
498
5
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 452 publications
(570 citation statements)
references
References 32 publications
49
498
5
3
Order By: Relevance
“…A similar film thickness is expected on the AuNPs as on the planar gold substrates (< 3 nm), since curvature effects are relatively small on 15-nm particles. [30] Despite the thin film thickness and the low molecular weight of 2 and 3 they provide excellent steric stabilization, due to their specific anchoring to the nanoparticle surface and favorable interactions with water molecules as was indicated in the IR water absorption bands. The shift in LSPR peak position (<1 nm for both AuNP-2 and AuNP-3) in 5 M NaCl is smaller than expected indicating that ions do not penetrate to a very large extent into the film.…”
Section: Immobilization On Gold Nanoparticlesmentioning
confidence: 99%
“…A similar film thickness is expected on the AuNPs as on the planar gold substrates (< 3 nm), since curvature effects are relatively small on 15-nm particles. [30] Despite the thin film thickness and the low molecular weight of 2 and 3 they provide excellent steric stabilization, due to their specific anchoring to the nanoparticle surface and favorable interactions with water molecules as was indicated in the IR water absorption bands. The shift in LSPR peak position (<1 nm for both AuNP-2 and AuNP-3) in 5 M NaCl is smaller than expected indicating that ions do not penetrate to a very large extent into the film.…”
Section: Immobilization On Gold Nanoparticlesmentioning
confidence: 99%
“…This modular structure enables researchers to program the length of DNA surface ligands with subnanometer precision based on the number of nucleobases. Control of surface ligand length and orientation is enhanced with double-stranded rather than single-stranded DNA, which increases the persistence length from 2 nm to 50 nm (55), and with increased surface density, wherein the polymer brush effect aligns and extends surface ligands (7,44,48,54,56). Tunable length allows precise control of interparticle spacing in nanoparticle crystallization experiments and sequence specificity allows one to program in chemical complementarity into surface ligands, which can be used to specifically cocrystallize nanoparticles of different sizes, shapes, and compositions (57,58).…”
Section: Ligands Arranged On Nanoparticle Surfacesmentioning
confidence: 99%
“…Ressine et al (2007) used porous silicon as a scaffold for antibody arrays and obtained detection limits down to 1 picomolar for IgG and 20 picomolar for prostatespecific antigen (PSA) in clinical samples. Hill et al (2009) explored the curvature effect of spherical gold nanoparticles on the loading density of probes. They showed that the binding to the nanoparticle surface is similar to that of a planar structure when the diameter of the particle is greater than 60 nm.…”
Section: Nanostructured Surfacesmentioning
confidence: 99%